Assessment of Postoperative Nurse’s Intervention in Patients with Laparoscopic Cholecystectomy at Teaching Hospitals in Sulaimaniyah, Iraq - Hassan, Heshu Dhahir; Saeed, Kamal Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Laparoscopic cholecystectomy is the standard gold treatment for gallstones. However, its postoperative complications can be overcome through highquality knowledge and practice of health care providers, especially nurses working at surgical wards that play major roles in post-operated patient management. Objective: This descriptive cross-sectional study aimed to assess the postoperative nurses' intervention for patients with laparoscopic cholecystectomy and to determine the relationship between nurses' interventions and their sociodemographic characteristics. Patients and Methods: A total of 65 experienced nurses at surgical wards in Sulaimaniyah Teaching Hospitals were included from March to August 2022 to determine nurses' intervention domains in laparoscopic cholecystectomy. For this purpose, a well-designed questionnaire was used to collect the participant's data, including sociodemographic data and clinical data. Results: Most participating nurses (38.5%) were aged 30-39 years, females (66.2%), from the urban region (87.7%), married (66.2%), completed nursing institute (76.9%), and full-time hospital staff (66.2%). Also, most (36.9%) had 1-5 years of work experience and did not take part in training courses (50.8%). In comparison, 41.5% of them participated in the training courses for <6 months. Furthermore, most of the studied variables for the postoperative nurses’ intervention items were significantly/highly significantly associated between the first and second assessments. Moreover, a significant difference between gender, education, and residency in the overall assessment of postoperative nurses’ intervention in the first assessment and a significant association only for residency was reported for the second assessment. Conclusions: Nurses who worked at surgical wards were professional in relieving pain, improving respiratory status, maintaining skin integrity/drainage, improving nutritional status, and monitoring/managing potential complications for patients who underwent laparoscopic cholecystectomy, regardless of their sociodemographic variables.
Keywords: Cholecystectomy; laparoscopy; gallstone; laparoscopy; nurses intervention